INNOVATIVE METHODS IN FORMING STUDENTS' CREATIVE ABILITY (Universal International Scientific Journal, 2026)
This article scientifically analyzes the current issues of developing creativity in students of secondary educational institutions and the pedagogical factors influencing it. In contrast to the traditional educational system, which relies solely on memory, the didactic possibilities of innovative approaches that stimulate originality in student thinking, in particular, STEAM education, project-based learning (PBL), and design thinking methods, are studied.
Keywords: : creativity, innovative education, creative thinking, divergent thinking, project-based learning, STEAM approach, modern pedagogical technologies.